Investigation of Mean Platelet Volume as a Prognostic Criterion in Non-Healing Wounds - Tutak, Fatma Nilay; Doğan, Fatih; Vural, Aşkı (Acta Medica, 2022)
Objective: We aimed to evaluate if the Mean Platelet Volume (MPV) is an acute phase reactant in non-healing wounds, by analyzing its correlation with Erythrocyte Sedimentation Rate (ESR). Method: Our study was carried out in a descriptive type with the participation of patients with non-healing wounds. The laboratory data and characteristics of the patients were accessed retrospectively, and the obtained data were recorded in the data recording form. Results: The sample group consisted of 92 patients with non-healing wounds. 26.9% of the patients with non-healing wounds had pressure sores, 37.6% of them had diabetic foot wounds, 18.3% had non-healing wounds developed after trauma, and 17.2% had necrotizing fasciitis. The average age of the patients was 53.22±19.13, and the average length of stay in the hospital was 108.98±18.78 (min 3 months, max 6 months) days. The MPV value, which was found to be high in the early stages of non-healing wounds, decreased after the wound was completely healed. When the MPV value was compared to ESR, an acute phase reactant, a positive and strong statistically significant correlation was found between MPV and ESR based on the result of this correlation analysis (r=0.256, p<0.01). Conclusion: MPV can be used as a marker, just like ESR, in the presence of non-healing wounds. MPV value can be measured with blood taken into the complete blood count. However, an extra blood sample and a different tube are required for ESR. Using MPV value instead of ESR will provide savings in terms of cost and labor.